'Mommy, You are the Princess and I am the Queen': How Preschool Children's Initiation and Language Use During Pretend Play Relate to Complexity. Issue 2 (15th July 2015) - Melzer, Dawn K.; Palermo, Cori A.
Abstract : The present study investigated the relationship between complexity of pretend play, initiation of pretense activities, and mental state utterances used during play. Children 3 to 4 years of age were videotaped while engaging in pretend play with a parent. The videotapes were coded according to mental state utterances (i.e. desire, emotion, cognitive, and modulations of assertion), and pretend play complexity (i.e. interaction with parent, object use, theme, and role transformation). Children who initiated the pretend activities exhibited more complex play behaviours than those whose parents initiated the activities. Children's increased use of cognitive mental state terms was related to increased pretend play complexity, while parents' increased use of cognitive terms was related to decreased levels of complexity. The results provide support for using a guided participation approach to interacting with preschool children to enhance independence and complexity in play. Copyright © 2015 John Wiley & Sons, Ltd.